A Randomized, Open-Label, Two-Way Crossover, Single-Dose Bioequivalence Study of Temozolomide 200 mg/m2 (Dralitem® vs. Temodal® Capsules) in Patients with Primary Tumors of the Central Nervous System Under Fasting Conditions - Muggeri, Alejandro (2017)
Background: Temozolomide is an antineoplastic agent of proven efficacy against high-grade gliomas. Purpose: The objective of this crossover, single-dose, bioequivalence study was to compare the rate and extent of absorption of oral temozolomide after administration of the study product (Dralitem®, Monte Verde Sociedad Anónima) and the reference product (Temodal®, originator product manufactured by Schering Plough Laboratories) in patients with primary central nervous system (CNS) tumors under fasting conditions. Methods: Sixteen male and female subjects with primary CNS tumors (excluding CNS lymphoma) were recruited, and were administered temozolomide 200 mg/m2 (Dralitem®) on days 1, 2 and 5 of a 5-day treatment. On days 3 and 4, subjects received the same dose of the test product (Dralitem®), or the reference product (Temodal®) on alternate days. The single dose of 200 mg/m2 was reached with three different temozolomide capsule strengths: 20, 100 and 250 mg. On days 3 and 4, blood samples were obtained for pharmacokinetic (PK) evaluation after drug administration. Results: Bioequivalence assessment was made for the 90% confidence interval (CI) for the ratio of log-transformed means (μT/μR) of the area under the concentration–time curve (AUC from time zero to the final quantifiable sample [AUCt] and AUC from time zero to infinity [AUC∞]) and maximum concentration (Cmax) of both the test (Dralitem®) and reference (Temodal®) products. The point estimate and 90% CI of the ratios of Cmax, AUCt and AUC∞ values were 94.37 (82.69–107.69), 100.99 (97.81–104.28) and 101.53 (98.60–104.54), respectively. The ratio met the predefined bioequivalence criteria (i.e. 90% CI between 80.00 and 125.00) for Cmax and AUC. The most commonly reported adverse events (AE) on this study were vomiting, abdominal pain, asthenia and weakness. One subject experienced expressive aphasia, possibly unrelated to the study drug and with no significant sequelae upon recovery. No serious AEs or unexpected AEs were reported. Conclusions: Temozolomide Dralitem® capsules, 20, 100 and 250 mg, were bioequivalent to Temodal® capsules under fasting conditions in patients with CNS primary tumors, supporting that they are therapeutic equivalents. ClinicalTrials.gov Identifier: NCT02343081.